Reaksi Pasar Terhadap Penerapan Kebijakan Pembatasan Sosial Berskala Besar Tahap I Perusahaan Sektor Kesehatan BEI - Maharani, Ida Ayu Surya; Putra, I Made Pande Dwiana (E-Jurnal Akuntansi, 2022)
This study aims to prove the information content of the implementation of the Phase I PSBB policy in Indonesia, which caused a market reaction as indicated by the abnormal return in the health sector on the Indonesia Stock Exchange. The observation period is carried out for 11 working days on the Indonesia Stock Exchange. This research is a type of event study research which is used to measure market efficiency and the impact of an event. The method of determining the sample in this research is non-probability sampling method and the sampling technique is using purposive sampling technique with a total sample of 17 companies. The results of the one sample t-Test test showed that the market had a significant positive reaction to the event that the implementation of the PSBB policy phase I on health sector companies on the Indonesia Stock Exchange was rejected, which means the market did not react to the event. Keywords:  PSBB; Market Reaction; Event Study; Abnormal Return.